Les bains-douches scolaires - Pauline Rossi (In Situ)
In 2020, the services of the City of Paris discovered a bathhouse facility in the basement of a school in the fourteenth arrondissement. This bathhouse was clearly intended not for adults but for the pupils at the school. In the historiography of school architecture, well studied by the architectural historian Anne-Marie Châtelet, the question of how hygiene was taught at school is one that has been little researched. An enquiry was undertaken, exploiting the resources of various departments within the municipal administration and aiming at drawing up an inventory of surviving bathhouse installations in Paris schools. Only two such facilities were identified, the first at the school of the fourteenth arrondissement (12, rue d’Alésia) and the other in the second arrondissement (5 rue Beauregard).At the same time as this enquiry, archival research allowed for the context of these forgotten installations to be better understood, giving a clearer picture of how many similar installations might have existed in the capital. The research was not exhaustive, but it allowed for the creation of an indicative inventory, identifying twenty such installations created between 1880 and 1930. Here then is the discovery of an important subject both for the built heritage of Paris schools and for the history of how hygiene was taught at school.